PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI MEDIA MATCHING GAME PADA ANAK KELOMPOK B DI TAMAN KANAK-KANAK ISLAM AL-AMANAH PROVINSI BENGKULU - Sri Praptini; Indra Yeni (STKIP Subang, 2026)
The purpose of this study is to improve children's ability to recognize number concepts through Matching Game media based on the Wordwall digital platform. This study is motivated by the low ability to recognize number concepts in Group B2 children at Al-Amanah Islamic Kindergarten, Bengkulu Province, which is caused by the use of learning media in understanding number concepts that tend to be conventional and monotonous. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of planning, implementation, observation and reflection stages. The subjects of this study were 12 children from Group B2. Data collection techniques were carried out through observation of research instruments through checklists and action documentation. The results of the study showed a gradual and significant increase in children's cognitive abilities in each cycle based on the class percentage assessment criteria. In the initial conditions, the average ability of children's development scores only reached 13.3 with a class percentage of 47% (Sufficient category), and the classical completion level was at 25% (Poor category). After intervention at the end of Cycle I, the average score for children increased to 19.3, with a class percentage of 69% (Good category), and the classical completion rate climbed to 58% (Good category). Children's cognitive development reached optimal performance at the end of Cycle II, with an average class score of 24.4 and a class success rate of 87% (Very Good category). Similarly, the classical completion rate at the end of Cycle II successfully reached the absolute target of 100% (Very Good category), with all 12 students successfully completing the task with the grade of